Guinea-Bissau : 2002 Article IV Consultation-Staff Report. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that in 2001, Guinea-Bissau suffered a substantial slowdown in economic activity, with real GDP growth estimated at 0.2 percent, as a result of a sizable loss of foreign program financing, a drop in the international market prices for cashew nuts of about 30 percent, and delays in implementing the demobilization and pre-2000 domestic arrears settlement programs and receiving the concomitant disbursements. Delays in implementing required structural reforms have contributed significantly to Guinea-Bissau's current difficulties.